Correlation Analysis between Platelet Aggregation and Neurological Outcomes in Ischemic Stroke Patients - Nurindar, Muyadhil; Muhiddin, Rachmawati A.; Muhadi, Darwati; Muis, Abdul; Nurulita, Asvin; Patellongi, Ilham Jaya (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Ischemic stroke is a condition triggered by cerebral perfusion disorders with the risk factor of blood clotting disorders that can cause neurological deficits through a complex pathophysiological process of thrombus formation. The role of platelet aggregation as a blood clotting parameter has the potential to be used as a marker for the level of neurological deficit in patients with ischemic stroke in conjunction with the National Institutes of Health Stroke Scale (NIHSS). The study aimed to observe the correlation between platelet aggregation and the degree of neurological deficit calculated using NIHSS. The study utilized a cross-sectional design with 51 research subjects diagnosed with ischemic stroke based on CT Scan results, followed by platelet aggregation testing. Patients with a diagnosis of hemorrhagic stroke and cardiogenic ischemic stroke were excluded from this study. This study found variations in platelet aggregation among groups with different degrees of stroke severity. However, it was not statistically significant (p=0.427). Correlation analysis showed a mild positive correlation between platelet aggregation and the degree of neurological deficit (r=0.157), although it was not statistically significant (p=0.270). There are variations in platelet aggregation in assessing neurological deficits using NIHSS. There is a positive correlation between the percentage of platelet aggregation and the level of neurological deficit in patients with ischemic stroke.